The Components Of Systematic Risk And Their Determinants In The Malaysian Equity Market - Hooy , Chee Wooi; D. Brooks, Robert (Asian Academy of Management (AAM), 2015)
We examine the country components of world systematic risk in the context of Bursa Malaysia. World systematic risk is divided into the US, developed markets, regional markets, major trading partners, and the rest of the world. We tested market and 9 firmcharacteristic-sorted portfolios, based on size, value and liquidity. Using monthly data for the 1988–2010 period, our analyses show that the US and regional factors are the most important sources of systematic risk. Tracing the time-varying betas of the US and regional factors, we find that they are driven by economic risk and financial risk, respectively